The SPICY FOOD: ITS EFFECT ON DYSPEPSIA COMPLAINTS AMONG UIN SUMATERA UTARA STUDENTS - Tiana, Triswa; Harahap, Anita Adelia Rahmah; Hati, Widya Puspita; Hanafi , Syahida Tahniah; Wahyudi, Wahyudi (HEARTY, 2025)
Background: Dyspepsia is a common complaint of pain or discomfort in the upper abdomen. In Indonesia, the prevalence of dyspepsia is very high, reaching 40-50% of the population. This study aims to determine the effect of spicy food consumption on the incidence of dyspeptic complaints in students of the State Islamic University of North Sumatra (UINSU). Methods: This study’s type of research is descriptive-analytic with a Cross-Sectional design. The respondents amounted to 89 people selected using the Accidental Sampling technique. The research instrument was a closed questionnaire distributed online using Google Forms. The data source is primary data. Data analysis includes univariate and bivariate analysis with the Chi-square test. Results: From a total of 89 respondents, the majority of respondents’ spicy food consumption level fell into the frequent category, namely 57 people (64.0%), and the majority of positive respondents experienced dyspepsia complaints, namely 52 people (58.4%). This study shows there is a significant relationship between spicy eating habits (p=0.000) with the incidence of dyspepsia in UINSU students. This study found that OR 6.306 means that students who often eat spicy food have a six times greater risk of experiencing dyspepsia than those who rarely consume it. Conclusion: This study conducted at UINSU revealed a strong association between spicy food consumption and increased incidence of dyspeptic complaints among university students, and those who frequently eat spicy food have a six times greater risk of developing dyspepsia than those who rarely consume it.